Essays on domestic market integration, government expenditure, and strategic interactions among local governments - Zhang, Cheng (2017)
This thesis contains one literature review chapter and three self-contained empirical studies on different but closely related topics, domestic market integration, public spending, and strategic interactions in China. In Chapter 1, we describe the general background of the Chinese fiscal reforms in the 1980s. In particular we present how the open-door policies has resulted in China’s increasing participation in the global market while at the same time its domestic market seem to still suffer from prevalent border effects and local protectionism. Besides, we outline the nature and source of this fragmentation, which stems from the fiscal and administrative decentralisation, that the fiscal reforms brought about, and the existing political system. As such the fiscal and administrative system give strong incentives for local governments to actively participate in yardstick competition, which often takes the form of the so-called ‘tournament competition‘. Chapter 2 provides a general overview of the existing literature on measuring domestic market integration (DMI). It provides the theoretical underpinnings and empirical evidence of this literature, organising DMI into three main streams of the literature, which are factor-related approach, price-related approach and output and employment-related approach. Chapter 3 adopts a spatial border difference approach and a spatial border econometric approach to estimate the provincial border effects and thus infer the degree of domestic market integration in China. By using a dataset of 48 border counties and 28 2-digit industries in the Yangtze River Delta region over the time period 2005-2009, we find that border effects are present and significant and also varying across provinces and industries. On average Shanghai shows the highest level of local protectionism with its provincial border exerting greater influences on the industry patterns compared with the other two provinces. We also observe the provincial border effects are decreasing over time, albeit over a short time period, which indicates an ongoing process of deepening market integration. Moreover, we also find that Jiangsu exhibits a higher level of border effects against Shanghai and Zhejiang than that with its all surrounding neighbours. Chapter 4 looks into the role of domestic market integration and socio-economic globalisation play in the size and structure of the public sector in China. By employing a dataset of 27 Chinese provinces for the period of 1998-2006, we find that domestic market integration has negligible effects, only showing a small positive correlation with social aspects of spending. On the other hand, the results of international integration provide some support for the ‘efficiency’ hypothesis over the ‘compensation’ view. More specifically, economic integration contributes to the overall expansion of public sector and in particular it increases productive and non-social spending, while social integration results in a reduction in total spending and social spending. Chapter 5 investigates the relationship between strategic interactions and political tournament competition in China. By using the provincial-level data for 28 Chinese provinces over the period of 1998-2005, we provide strong evidence of the spatial autocorrelation in both total spending and its components, though we fail to find evidence supporting the ‘tournament competition’. Besides, the spending level in neighbouring provinces acts as a constraining effect on a local leader’s promotion. Moreover, we found that a higher level of total spending, productive spending and education spending compared with their contiguity neighbours, and a higher level of agriculture spending compared with their GDP-related neighbours would significantly increase the promotion opportunities of provincial governors. In contrast, the level of administration spending relative to local province’s GDP-related neighbours and the level of agency spending relative to geographic-related neighbours are negatively linked with the political turnover rate of provincial governors. Chapter 6 summarises the main findings of the thesis and outline the policy implications of our findings.